Copper(II) complexes with a benzimidazole functionalized Schiff base: Synthesis, crystal structures, and role of ancillary ions in phenoxazinone synthase activity. (16th February 2021) - Mudi, Prafullya Kumar; Mahato, Rajani Kanta; Joshi, Mayank; Shit, Madhusudan; Choudhury, Angshuman Roy; Das, Hari Sankar; Biswas, Bhaskar
Abstract : This research study reports the synthesis, structural characterization and phenoxazinone synthase‐like activity of two structurally similar copper(II) complexes developed with a benzimidazole functionalized Schiff base (L ). The ligand, L, was designed and synthesized in high yield by the reaction of p ‐methoxy benzaldehyde with o ‐phenylenediamine. The reaction of L with CuCl2 and Cu(NO3 )2 leads to the formation of two isostructural complexes, [Cu(L )2 Cl2 ]2 (1 ) and [Cu(L )2 (NO3 )2 ]2 (2 ). Single crystal X‐ray structural study reveals that both the Cu(II) centre in 1 and 2 adopts a square planar geometry. An attempt has also been made to understand the role of coordinated co‐ligands on the catalytic oxidation of 2‐aminophenol (2‐AP) to 2‐amino‐3 H ‐phenoxazine‐3‐one (2‐APX) in methanol. The presence of coordinated nitrate to Cu(II) ions imparts a more labile character to complex 2, and the catalytic efficiency ( k cat /KM ) for complex 2 (1.50 × 10 7 ) was determined almost double compared with that of complex 1 (8.78 × 10 6 ). Electro‐chemical and electrospray ionization mass spectrometry studies of 1 and 2 with 2‐AP suggests that the square planar geometries of the Cu(II) centres remain the driving force to develop enzyme‐substrate adducts and excellent catalytic performance of the complexes. Electrochemical and EPR spectral analysis of the reaction mixture confirm the presence of active 2‐AP − /2‐AP − redox species in the course of catalytic oxidation and suggest the radical driven oxidative coupling of 2‐AP in an aerobic environment. Temperature‐dependent kinetic measurements were carried out to evaluate the activation parameters ( E a, Δ H ‡, Δ S ‡ ), which favours the higher rate of catalytic oxidation of 2‐AP for complex 2 than complex 1 . Abstract : This research work reports the synthesis, structural characterization and phenoxazinone synthase activity of two structurally similar copper(II)–benzimidazole complexes.